Ethics and ethical theories from an Islamic perspective - Al-Aidaros, Al-Hasan; Mohd Shamsudin, Faridahwati; Md. Idris, Kamil (Universiti Kebangsaan Malaysia, 2013)
With the collapse of many organizations, many researchers are increasingly paying attention to such phenomenon.But ethical issues are not always clear cut; there are many grey areas that need to be threaded with care by organizations.To determine whether an action or decision is ethically carried out, ethical theories, developed mainly by Western scholars, are the current theoretical framework organizations have at their disposal. Theories such as relativism, utilitarianism, egoism, deontology, the divine command theory, and the virtue ethics, are all products of Western understanding of what ethics are and how they are applicable to help one’s decision making process.Despite their utility, this paper intends to argue that the Western concepts and understanding of what ethics are limited and in comprehensive in explaining what is right and what is wrong.In its place, this paper argues that to understand the concepts of ethics that can extend beyond time and space.It has to be analysed from an Islamic perspective.Toward this purpose, this paper will compare and contrast between Islamic and Western perspectives of ethics, and highlight the main weaknesses and limitations of the former.Then, an argument on why Islam can provide the best understanding of ethics will be made.